Крейцерова соната: [сборник] / Л. Н. Толстой - Толстой Лев Николаевич (Великие произведения о любви, 2015)
Экземпляры: Ф-17 (20230411) / Инвентарный номер: 98467 / Цена: / Сис.шифр: 84(2=411.2)-4 / Авт.знак: Т 53 / ГРНТИ: 17.82.30 / ББК: 84(2=411.2)-4